2022
DOI: 10.3390/cells11010177
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Cystinotic Kidney Tubules Recapitulate a Nephropathic Phenotype

Abstract: Nephropathic cystinosis is a rare and severe disease caused by disruptions in the CTNS gene. Cystinosis is characterized by lysosomal cystine accumulation, vesicle trafficking impairment, oxidative stress, and apoptosis. Additionally, cystinotic patients exhibit weakening and leakage of the proximal tubular segment of the nephrons, leading to renal Fanconi syndrome and kidney failure early in life. Current in vitro cystinotic models cannot recapitulate all clinical features of the disease which limits their tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Mutations in this gene result in nephropathic cystinosis, a chronic condition in which lysosomal accumulation of cystine leads to loss of PT integrity (figure 1(A)). Furthermore, it has been demonstrated that a 3D membrane-based model of ciPTEC CTNS -/recapitulated better the nephropathic phenotype at a molecular, structural, and functional PT level compared to 2D cell cultures [10]. This observation highlights the importance of using a biomimetic microenvironment to recapitulate kidney functions.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Mutations in this gene result in nephropathic cystinosis, a chronic condition in which lysosomal accumulation of cystine leads to loss of PT integrity (figure 1(A)). Furthermore, it has been demonstrated that a 3D membrane-based model of ciPTEC CTNS -/recapitulated better the nephropathic phenotype at a molecular, structural, and functional PT level compared to 2D cell cultures [10]. This observation highlights the importance of using a biomimetic microenvironment to recapitulate kidney functions.…”
Section: Introductionmentioning
confidence: 78%
“…Tight sealing of our engineered chip was confirmed by perfusing colored MilliQ water through a microfiber not containing cells (supplementary movie 1). It has been previously demonstrated that CTNS -/cells grown on hollow fiber membranes form a less tight monolayer in comparison to a healthy control [10]. Here, we evaluated cell monolayer tightness by means of an inulin-FITC leakage assay.…”
Section: Healthy and Cystinotic Ciptec Form Tight Monolayers In Coaxi...mentioning
confidence: 98%
See 1 more Smart Citation
“…4,21 The hollow fiber membrane (HFM) 3D model is representative of a functional kidney tubule and was prepared by seeding PTECs on L-DOPA and Collagen-IV coated fibers at 33°C, as described. 22 Experiments were performed after differentiation at 37°C for 10 (PTECs) or 12 days (PODOs).…”
Section: Cell Culturementioning
confidence: 99%
“…HFM were also stained for the 3HA-tag, F-actin and LAMP1, according to previously described protocols. 22 Cystine measurement in vitro Cystine levels were measured, as described previously, 21 in a total volume of 100µL 50mM Nethylmaleimide (Sigma, cat.no.04259) and 50µL of 12% sulfosalicylic acid (Sigma, cat.no.S7422).…”
Section: Transfection Efficiency and Protein Localizationmentioning
confidence: 99%